Does substance use affect educational outcomes? - Daniel I. Rees (IZA World of Labor, 2014)
A non-trivial portion of traffic fatalities involve alcohol or illicit drugs. But does the use of alcohol and illegal substances—which is linked to depression, suicide, and crime—reduce academic performance? Recent studies suggest that drinking has a negative, if modest, effect on grades, and although students who use illegal substances are more likely to drop out of school, this may reflect the influence of difficult-to-measure factors at the individual level, such as personality.
Keywords: I1; I2; K4; 330; alcohol; marijuana; school dropout; human capital; grade point average